ANALISIS PENGEMBANGAN MEDIA DALAM PEMBELAJARAN KIMIA - Chusnur Rahmi; Ana Fitria; Vivit Santika; Sri Rahmawati (Lantanida Journal, 2022)
Media plays an important role in the chemistry learning process. The development of media in chemistry learning can help teachers increase students' knowledge and interest in learning. This study aims to determine the development of media in chemistry learning in terms of the types of media, development methods, and chemical materials. This research uses literature study method. The data analyzed in this study are the results of research from 26 articles on media development in chemistry learning that have been published in national journals. The results showed that in chemistry learning, visual-based media, inquiry-based media, video-based media, application-based media, and interactive media have been developed. Learning media was developed using the Research and Development (R&D) method with Borg and Gall, 3D, 4D, and ADDIE development models. Android-based media is the most popular as a medium for chemistry learning. The ADDIE development model is the most widely used in developing chemistry learning media. The development of learning media accommodates 30.8% of class X chemistry, 46.2% of class XI chemistry, and 23.1% of class XI chemistry.